Imaged based identification of colombian timbers using the xylotron: A proof of concept international partnership - Arévalo, Rafael; Pulido R., Esperanza N.; Solórzano G., Juan F.; Soares, Richard; Ruffinatto, Flavio; Ravindran, Prabu; Wiedenhoeft, Alex C. [UNESP] (Universidad Distrital Francisco Jose de Caldas, 2021)
Field deployable computer vision wood identification systems can be relevant in combating illegal logging in the real world. This work used 764 xylarium specimens from 84 taxa to develop an image data set to train a classifier and identify 14 commercial Colombian timbers. We took images of specimens from various xylaria outside Colombia, trained and evaluated an initial identification model and then collected additional images from a Colombian xylarium (BOFw) and incorporated these images to refine and produce a final model. The specimen classification accuracy of this final model was ~ 97%, which demonstrates that including local specimens can augment the accuracy and reliability of the XyloTron system. Our study demonstrates the first deployable computer vision model for wood identification in Colombia, which is developed on a timescale of months rather than years by leveraging on international cooperation. We conclude that field testing and advanced forensic and machine learning training are the next logical steps.
Identificación de maderas colombianas utilizando el Xylotron: Prueba de concepto de una colaboración internacional
Keywords: Deep learning; Forensic wood anatomy; Machine Learning; Transfer learning; Wood identification